Cannabinoid CB1 Receptor Involvement in the Actions of CBD on Anxiety and Coping Behaviors in Mice - Amaya Austrich-Olivares; María Salud García-Gutiérrez; Lucía Illescas; Ani Gasparyan; Jorge Manzanares (MDPI AG, 2022)
The anxiolytic and antidepressant properties of cannabidiol (CBD) have been evaluated in several studies. However, the molecular mechanisms involved in these actions remain unclear. A total of 130 male mice were used. CBD's ability to modulate emotional disturbances (anxiety and depressive-like behaviors) was evaluated at different doses in wild-type (CD1; 10, 20 and 30 mg/kg; i.p.) and knockout (CB1KO, CB2KO; GPR55KO; 20 mg/kg) mice. Moreover, CBD effects (20 mg/kg; i.p.) were evaluated in mice previously treated with the CB1r-antagonist SR141716A (2mg/kg; i.p.). Relative gene expression analyses of Cnr1 and Cnr2, Gpr55 and GABA(A)α2 and γ2 receptor subunits were performed in the amygdala (AMY) and hippocampus (HIPP) of CD1 mice. CBD (10 and 20 mg/kg) showed anxiolytic and antidepressant actions in CD1 mice, being more effective at 20 mg/kg. Its administration did not induce anxiolytic actions in CB1KO mice, contrary to CB2KO and GPR55KO. In all of them, the lack of cannabinoid receptors did not modify the antidepressant activity of CBD. Interestingly, the administration of the CB1r antagonist SR141716A blocked the anxiolytic-like activity of CBD. Real-time PCR studies revealed a significant reduction in Cnr1 and GABA(A)α2 and γ2 gene expression in the HIPP and AMY of CD1 mice treated with CBD. Opposite changes were observed in the Cnr2. Indeed, Gpr55 was increased in the AMY and reduced in the HIPP. CB1r appears to play a relevant role in modulating the anxiolytic actions of CBD. Moreover, this study revealed that CBD also modified the gene expression of GABA(A) subunits α2 and γ2 and CB1r, CB2r and GPR55, in a dose- and brain-region-dependent manner, supporting a multimodal mechanism of action for CBD.